2014
DOI: 10.1155/2014/724838
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of IKK Inhibitor XII, Thymulin, and Fat-Soluble Antioxidants in LPS-Treated Mice

Abstract: The present study was designed to compare the anti-inflammatory effects of several agents applied in vivo, namely, a synthetic inhibitor of the NF-κB cascade, fat-soluble antioxidants, and the thymic peptide thymulin. Cytokine response in LPS-treated mice was analysed in tandem with the following parameters: the synthesis of inducible forms of the heat shock proteins HSP72 and HSP90α; activity of the NF-κB and SAPK/JNK signalling pathways; and TLR4 expression. Inflammation-bearing Balb/c male mice were pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This is an additional evidence to indicate the ability of the PTs to inhibit the IKK-mediated NF-κB activation and the subsequent suppression of the pro-inflammatory cytokines. Our findings are in accordance with the results from an earlier in vivo study in the LPS-treated mice [ 90 ]. Modulation of the LPS-induced NF-κB signaling by the PTs along with the proposed mechanisms is presented as schematics in Fig 9 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is an additional evidence to indicate the ability of the PTs to inhibit the IKK-mediated NF-κB activation and the subsequent suppression of the pro-inflammatory cytokines. Our findings are in accordance with the results from an earlier in vivo study in the LPS-treated mice [ 90 ]. Modulation of the LPS-induced NF-κB signaling by the PTs along with the proposed mechanisms is presented as schematics in Fig 9 .…”
Section: Discussionsupporting
confidence: 93%
“…The increase in the IKK/NF-κB activity has a critical role in LPS stimulated inflammation. The pretreatment of the LPS treated mice with the IKK inhibitor XII decreases the plasma levels of the IFN-γ, a pro-inflammatory cytokine [ 90 ]. This study substantiates the significance of the IKK inhibition in delaying the proinflammatory response in the LPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…IKBKB is a positive regulator of the inflammatory response and an important upstream modulator of NF-kB pathway. Its inhibition reduces the inflammatory response and pro-inflammatory cytokine production in response to LPS (Novoselova et al, 2014), and may contribute to diminished ability of DFUs to respond to pathogens. By suppressing the key regulator gene IKBKB, S. aureus -induced miR-15b-5p may affect multiple signaling pathways including NF-KB, IL6, IL8, IL12, PI3K/AKT, and PTEN (Ding et al, 2013, Li et al, 2010) contributing to suppression of the inflammatory phase of wound healing, which is required for a proper healing response and clearing bacterial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we aimed to study the effects of thymulin on immune cell activity in a mouse model of chronic inflammation induced by daily treatment with increasing doses of LPS. Based on our earlier investigations, in which thymulin was found to have anti-inflammatory properties in vitro [ 21 ] and in acute inflammation in vivo [ 31 ], we concluded that it might exert a protective effect against the consequences of sepsis. It is important to emphasize that when applied to healthy mice, thymulin does not affect plasma levels of proinflammatory cytokines, synthesis of stress proteins (Hsp70 and Hsp90), or cellular production of nitric oxide [ 31 ].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we also extensively studied the role of thymic peptides in the pathogenesis of sepsis [ 19 ]. For the first time, we revealed that the anti-inflammatory effects of such peptides are mediated by the activity of several intracellular signaling pathways [ 20 ], and that one of these peptides, thymulin, increases the anti-inflammatory activity of a specific inhibitor of the NF-κB signaling pathway, IκB kinase (IKK) inhibitor XII, in mice with acute septic inflammation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%